Model of factors affecting organizational culture on business performance: A case study of small and medium enterprises in the Mekong Delta - Dang, Xuân Châu (Tập san Khoa học và kỹ thuật trường Đại học Bình Dương, 2023)
The study was conducted with the aim of analyzing the influence of factors affecting organizational culture on business performance: The case of small and medium-sized enterprises in the Mekong Delta region, Kowloon. The study identified five factors and proposed a research model for factors synthesized from relevant research reviews, including: Mission, Adaptability, Remuneration policy, Working environment , Corporate branding. After discussing with experts to adjust the appropriateness of factors affecting organizational culture to business performance.